Structural variety of arginine-rich RNA-binding peptides. - Tan, R (1995)
Arginine-rich domains are used by a variety of RNA-binding proteins to recognize specific RNA hairpins. It has been shown previously that a 17-aa arginine-rich peptide from the human immunodeficiency virus Rev protein binds specifically to its RNA site when the peptide is in an alpha-helical conformation. Here we show that related peptides from splicing factors, viral coat proteins, and bacteriophage antiterminators (the N proteins) also have propensities to form alpha-helices and that the N peptides require helical conformations to bind to their cognate RNAs. In contrast, introducing proline mutations into the arginine-rich domain of the human immunodeficiency virus Tat protein abolishes its potential to form an alpha-helix but does not affect RNA-binding affinity in vitro or in vivo. Based on results from several peptide-RNA model systems, we suggest that helical peptides may be used to recognize RNA structures having particularly wide major grooves, such as those found near loops or large bulges, and that nonhelical or extended peptides may be used to recognize less accessible grooves.